CO₂ emissions in G20 Nations through the three-sector model - Kejia Yan; Rakesh Gupta; Victor Wong (Journal of Risk and Financial Management, 2022)
This paper examines the relationship between CO2 emissions in three economic sectors of G20 member countries using the environmental IPAT model and STIRPAT model and validates the EKC hypothesis by comparing the results for developing and developed countries. The results confirm that there is a significant long-run equilibrium relationship between the three sectors (primary, secondary, and tertiary) and CO2 emissions across the panel. Furthermore, the long-run elasticities suggest that the primary sector (agriculture) positively and negatively affects the CO2 emissions of developing and developed economies, respectively. This finding proves that the development of agriculture is in line with the EKC hypothesis that a more developed economy will instead improve environmental degradation. Based on the findings, for each sector, we provide policymakers with suggestions to potentially curb CO2 emissions without significantly compromising economic growth.
Keywords: 650; economic growth; curbing CO2 emissions; EKC; G20 nations; three-sector model